Synthesis, characterization and biological studies of S-4-methylbenzyl-β-N-(2-furylmethylene)dithiocarbazate (S4MFuH) its Zn2+, Cu2+, Cd2+ and Ni2+ complexes - Yusof, E.N.M.; Ravoof, T.B.S.A.; Jamsari, J.; Tiekink, E.R.T.; Veerakumarasivam, A.; Crouse, K.A.; Tahir, M.I.M.; Ahmad, Haslina (Elsevier, 2015)
S-4-methylbenzyl-β-N-(2-furylmethylene)dithiocarbazate (S4MFuH, 1) derived from the condensation reaction of furaldehyde (Fu) with S-4-methylbenzyldithiocarbazate (S4MBDTC) has been complexed with transition metal acetates to give Zn(S4MFu)2 (2), Cd(S4MFu)2 (3), Cu(S4MFu)2 (4) and Ni(S4MFu)2 (5). It is evident from the shift in ν(C=N) and ν(N-N) in the IR spectra of the complexes that deprotonated 1 acts as a bidentate ligand coordinating through the azomethine nitrogen and thiolato sulfur atoms. This was confirmed by single crystal X-ray diffractometry. The U-shaped dithiocarbazate 1 exists in the E configuration with the thione bond anti to the azo bond. A change in conformation is noted in the transition metal complexes resulting from deprotonation and N-S-chelation. 2 and 3 display a distorted tetrahedral geometry with the major cause of the distortion being two close intramolecular M...O interactions. Binding interaction studies with calf thymus DNA demonstrated that 4 also had the strongest DNA binding affinity (Kb = 2.85 × 104 M-1) among all compounds prepared in this work. The Cu(II) complex, 4, was also moderately active against estrogen receptor-positive breast cancer cells, MCF-7 (IC50 = 3.02 μM) while the remainder were inactive against MCF-7 and all showed no activity towards receptor negative breast cancer cells, MDA-MB-231.